A sensitive UPLC-APCI-MS/MS method for the determination of dexamethasone and its application in an ocular tissue distribution study in rabbits following topical administration. Issue 20 (11th April 2018) - Matta, Murali K.; Narayanasamy, Suresh; Thomas, Christopher D.; Xu, Lin; Stewart, Sharron; Chockalingam, Ashok; Patel, Vikram; Rouse, Rodney
Abstract : A sensitive, specific and rapid ultra-performance liquid chromatography tandem mass spectrometry method has been developed and validated for the determination of dexamethasone (DEX) in ocular tissues of rabbits. Abstract : A sensitive, specific and rapid ultra-performance liquid chromatography-atmospheric pressure chemical ionization tandem mass spectrometry (UPLC-APCI-MS/MS) method has been developed and validated for the determination of dexamethasone (DEX) in ocular tissues and biofluids of rabbits. Dexamethasone-d5 (DEX-d5 ) was used as an internal standard. Protein precipitation was used to extract the drug from ocular tissue homogenates, biofluids and plasma. Chromatographic separation was achieved on an Acquity C18 column (100 × 2.1 mm, 1.7 μm) using a gradient run with a mobile phase composed of methanol and 5 mM ammonium formate in 0.1% formic acid in water buffer at a flow rate of 0.5 mL min −1 . A detailed method validation in two matrices (bovine serum albumin and phosphate buffer) was performed as per the FDA guidelines and the calibration curve obtained was linear ( r 2 = 999) over the concentration range 200–100 000 pg mL −1 . A Sciex 6500+ coupled with a Waters Acquity UPLC (Ultra Performance Liquid Chromatography) system was operated in the multiple monitoring mode (MRM) during the analysis. The proposed method was applied to a rabbit ocular tissue distribution study after topical ophthalmic administration of dexamethasone and tobramycin suspension.